Developing a new model for rhinosinusitis: Animal experiment - OYSU, ÇAĞATAY (My University, 2023)
Aim: To develop a new model of acute bacterial rhinosinusitis. Method: We divided guinea pigs into four groups in this study. In the primary group of guinea pigs, right nasal cavities of the animals were vaccinated with Streptococcus pneumoniae suspension. In the second group, sponge strips saturated with sterile saline into the right nasal cavities of animals. In the third group, sponge strips saturated with Streptococcus pneumoniae suspension in the right nasal cavities of animals. The fourth group was control group, which was exposed to no intervention. After 7, 14, 28, 35 days from interventions, intranasal cultures were obtained, computed tomography (CT) scans were imaged from all of the guinea pigs, and two randomly selected guinea pigs that were detected as having rhinosinusitis radiologically were killed every week. The sinuses and nasal specimens of sacrificed guinea pigs were prepared for histopathological investigation. Results: Radiological and histopathological examinations of nasal samples were performed to observe the severity of the inflammatory reaction. Acute bacterial rhinosinusitis was induced in all groups of subject animals except the control group. More severe inflammation was seen in the third group of subject animals compared to the first and second groups. No inflammatory reaction was found in the control group. We also evaluated the normal flora of guinea pigs. Conclusion: The guinea pig is certainly a true model for developing rhinosinusitis. Guinea pigs should be considered as an alternative model for further potential studies of genetics and inflammation, even though surgical manipulation is limited.

Amaç: Yeni bir akut bakteriyel rinosinüzit modeli geliştirmektir. Yöntem: Çalışmada kobay hayvanlar dört gruba ayrılmıştır. Birinci gruptaki hayvanların sağ nazal kavitelerine Streptococcus pneumoniae süspansiyonu damlatılmıştır. İkinci grupta, steril serum emdirilmiş merosel şeritler hayvanların sağ nazal pasajlarına pasajı kapatacak şekilde yerleştirilmiştir. Üçüncü grupta, Streptococcus pneumoniae emdirilmiş merosel şeritler hayvanların sağ nazal kavitelerine yerleştirilmiştir. Dördüncü grup ise herhangi bir girişim veya işlem yapılmayan hayvanların bulunduğu kontrol grubudur. Girişimleri takiben 7., 14., 28., 35. günlerde intranazal kültürler incelenmiş, bilgisayarlı tomografi (CT) görüntüleri tüm kobay hayvanlarından alınmış, ve radyoloji olarak rinosinüsit tespit edilen hayvanlardan iki tanesi rastlantısal olarak seçilerek her hafta dekapite edilmiştir. Sakrifiye edilen kobayların sinüsleri ve nazal spesimenleri histopatolojik olarak incelenmiştir. Bulgular: Histopatolojik ve radyolojik incelemelerin yapıldığı nazal örneklemeler inflamatuar reaksiyonun ciddiyetini gözlemlemeyi sağlamıştır. Akut bakteriyel rinosinüzit, kontrol grubu hariç tüm gruplardaki kobaylarda indüklenmiştir. Üçüncü gruptaki kobaylarda ilk iki gruba nazaran daha ciddi bir inflamasyon gözlenmiştir. Kontrol grubunda herhangi bir inflamatuar reaksiyon bulunmamıştır. Ayrıca kobay hayvanlarının normal florası da incelenmiştir. Sonuç: Kobay hayvanı deneysel olarak rinosinüzit oluşturmak için çok uygun bir hayvan deneyi modelidir. Kobay hayvanı cerrahi manipülasyondaki kısıtlılığa rağmen, ilerdeki potansiyel genetik ve inflamasyon çalışmaları için alternatif bir model olacaktır.
Yeni bir rinosinüzit modeli geliştirmek: Bir hayvan deneyi
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Sinusitis; rhinosinusitis; guinea pig; animal experiment; Sinüzit; rinosinüzit; kobay hayvanı; gine pig; hayvan deneyi